Pengaruh Implementasi QRIS terhadap Efektivitas Sistem Pembayaran di Pemerintah Daerah: Studi Kasus pada Kantor Samsat Kota Kupang (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
The development of digital financial technology in Indonesia has encouraged the shift towards non-cash payment methods that are more practical, fast, and secure. One of the innovations introduced is the Quick Response Code Indonesian Standard (QRIS), which has been widely applied, including in public services. The Kupang City Government, through the Samsat Office, has implemented QRIS as a payment method for motor vehicle taxes to improve the effectiveness of the payment system. This study aims to analyze the effect of QRIS implementation on the effectiveness of the motor vehicle tax payment system at the Kupang City Samsat Office. This research employed a quantitative approach with a case study method. Primary data were collected through questionnaires administered to 40 taxpayers using QRIS and interviews with Samsat employees. Data were analyzed using simple linear regression. The results indicate that the implementation of QRIS has a positive and significant effect on the effectiveness of the payment system. QRIS has proven to simplify transactions, reduce queues, improve recording accuracy, and support transparency in local tax revenue collection. Interview findings also reinforce the quantitative results, showing that ease of use and time efficiency are the main factors for taxpayers choosing QRIS, despite challenges such as limited infrastructure in mobile Samsat services and low digital literacy among the community.